STUDI KOMPARATIF EUTHANASIA AKTIF SEBAGAI BENTUK EKSEKUSI BAGI TERPIDANA MATI YANG LEBIH MANUSIAWI DAN BERADAB - I Komang Mahardika Wijaya (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2023)
This research is a normative research (legal research) using the method of collecting library studies. This research topic is divided into two issues. The first topic is how to regulate the execution of executions in Indonesia and the second topic is whether the implementation of active euthanasia as a more humane and civilized form of execution.The Constitutional Court affirmed the inclusion of the death penalty both in the Criminal Code and outside the Criminal Code with Decision Number 21/PUU-VI/2008 which stated that the imposition of the death penalty did not contradict the Constitution. According to Article 99 (3) of the new Penal Code,